Correction: Juhás et al. Improving Antimicrobial Activity and Physico-Chemical Properties by Isosteric Replacement of 2-Aminothiazole with 2-Aminooxazole. Pharmaceuticals 2022, 15, 580 - Martin Juhás; Andrea Bachtíková; Daria Elżbieta Nawrot; Paulína Hatoková; Vinod Sukanth Kumar Pallabothula; Adéla Diepoltová; Ondřej Janďourek; Pavel Bárta; Klára Konečná; Pavla Paterová; Vít Šesták; Jan Zitko (MDPI AG, 2023)
In the original publication [...]